KEKOHESIFAN WACANA TAJUK RENCANA SURAT KABAR HARIAN PAGI JAMBI INDEPENDENT - Nurma Subekti (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
As written discourse, TR is required to have the structural integrity of discourse. Cohesion is needed in the formation of the unity of discourse. This, because the cohesive discourse can create a coherent discourse. The purpose of this study is to describe the types of discourse and describes the means of cohesion cohesiveness discourse editorial in the Daily Morning Newspaper Jambi Independent Edition March 2013. The method used in this research is descriptive quantitative method. The research data is the kind of cohesion means contained in the discourse editorial Newspaper Jambi Independent Daily Morning Edition March 2013. The data obtained with several steps, namely 1) collect discourse text in newspaper editorials Jambi Independent Daily Morning Edition March 2013, 2) sort text discourse editorial corresponding date of issuance to give the number and code on each editorial serve as research data, 3) read the whole discourse editorial studied to find the means of cohesion that build the discourse, and 4) mark with by highlighting the means of cohesion found in the discourse and record it into the record. As follows. (1) discourse contained in editorial Newspaper Jambi Independent Daily Morning Edition March 2013 using nine types of means of cohesion. The cohesion means is pronouns, substitution, ellipsis, conjunction, repetition, synonyms, hyponymy and hypernymy, collocation, and antonyms. Means cohesion are most commonly found are pronouns and conjunctions. Besides cohesion means the most widely used inappropriately is a conjunction. (2) The use of means of cohesion discourse cohesiveness editorial Newspaper Jambi Independent Daily Morning Edition March 2013 including the category of very cohesive, which is 93.9% and the use of cohesion means that no cohesive discourse Newspaper editorial Jambi Independent Daily Morning Edition March 2013, namely 6.1%.